Pseudoblothrus oromii - Nunes, Rui (2021)
JUSTIFICATION: Pseudoblothrus oromii is a cave-adapted species known from a single island, S. Jorge (Azores, Portugal). It has a very small Extent of Occurrence (EOO = 4 km²) and Area of Occupancy (AOO = 4 km²). The species is rare and only known from a single subpopulation in the lava tube of Gruta da Beira. The area surrounding the cave is heavily impacted by human activities. Further research is needed into its population, ecology and life history. A habitat management plan is needed and one is anticipated to be developed during the coming years. We also suggest as future measures of conservation the regular monitoring of the species (every ten years) and limiting access to the cave. The species is assessed as Critically Endangered (CR), mostly due to its small Extent of Occurrence (EOO) and Area of Occupancy (AOO) and the decline in habitat quality.